Situation Report: Poland, 4 October 1963 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Polish-East German Communique Marek Thee to Return to Poland Anniversary of Cracow [Kraków] University Polish-Greek Trade Agreements Polish-Mongolian Trade Protocol Trade Agreement between Poland and the Congo (Leopoldville) Other Trade News